Window film
By controlling the physical properties of the window film adhesive layer, the problem of residual glue generated during peeling of the window film is solved, the strong adhesion during adhesion and good releasability during peeling are achieved, and the requirements of anti-scattering and ultraviolet shielding functions are met.
Patent Information
- Application Number
- CN202380056801.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-03
- Publication Date
- 2025-03-18
AI Technical Summary
The window film is prone to residual glue when peeling, and the adhesion is unbalanced before and after peeling, making it difficult to take into account both strong adhesion and re-peelability.
By controlling the physical properties of the adhesive layer, the initial adhesion force at 23°C is ensured to be 1N/25mm or more, and the adhesion force after being placed at 80°C for 168 hours is 18N/25mm or less, and the change ratio of the energy storage modulus is controlled to be less than 3.5 to take into account both the strong adhesion during adhesion and the good releasability during peeling.
It realizes strong adhesion of the window film during adhesion and good releasability during peeling, avoids the generation of residual glue, and meets the needs of anti-scattering and ultraviolet shielding functions.
Smart Images

Figure CN119654387A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a window film. Background Art
[0002] Window films are adhesive films that are attached to windows of mobile objects such as automobiles and buildings in order to provide them with anti-scattering functions, ultraviolet and infrared shielding functions of sunlight, crime prevention performance, etc., and are widely used.
[0003] In order to fully exert the anti-scattering function, the window film needs to be sufficiently fixed to the window. In other words, the window film needs to be strongly adhered to the adherend (window, etc.).
[0004] On the other hand, a window film is sometimes peeled off and replaced with another window film after being attached to an adherend for a predetermined period of time. Therefore, it is desired that the window film to be peeled off does not leave adhesive residue on the surface of the adherend when peeled off (good re-peelability).
[0005] Therefore, a window film is required to have both strong adhesiveness and removability, which are contradictory properties.
[0006] Patent Documents 1 and 2 describe that an adhesive sheet can maintain good initial adhesive strength and good removability by including a specific compound in an adhesive composition.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 4236149
[0010] Patent Document 2: Japanese Patent No. 4376491 Summary of the invention
[0011] 1. Technical issues to be resolved
[0012] The inventor of the present application conducted an in-depth study and found that when the window film is peeled off from the adherend after a specified period of time, the adhesive force during peeling is much greater than the adhesive force during attachment due to the environmental load from attachment to peeling. As a result, it is easy to generate residual adhesive on the surface of the adherend.
[0013] In addition, the inventors of the present application have found that the phenomenon that the adhesive force becomes very large during peeling is related to the adhesive force in the time test at a temperature higher than room temperature. It has also been found that by making the adhesive force in the time test at a temperature higher than room temperature within a specified range, the re-peelability can be improved, and both strong adhesion and re-peelability can be achieved, thereby completing the present invention.
[0014] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a window film having an adhesive layer capable of achieving both strong adhesiveness during attachment and removability after a predetermined period of time.
[0015] (II) Technical solution
[0016] The scheme of the present invention is as follows.
[0017] [1] A window film comprising a substrate and an adhesive layer disposed on one main surface of the substrate,
[0018] After being placed at 23°C and 50% relative humidity for 24 hours, the adhesive layer has an adhesion to the float glass of 1N / 25mm or more.
[0019] The adhesive strength of the adhesive layer to the float glass after being left to stand at 80° C. for 168 hours was 18 N / 25 mm or less.
[0020] [2] The window film according to [1], wherein a ratio of the storage modulus of the adhesive layer at 23° C. to the storage modulus of the adhesive layer at 80° C. is 3.5 or less.
[0021] [3] The window film according to [1] or [2], wherein the adhesive strength of the adhesive layer to the float glass after being left at 60° C. and a relative humidity of 95% for 168 hours is 22 N / 25 mm or less.
[0022] [4] The window film according to any one of [1] to [3], comprising a hard coating layer disposed on the other main surface of the substrate.
[0023] [5] The window film according to any one of [1] to [4], wherein the window film has ultraviolet light absorptivity.
[0024] [6] The window film according to any one of [1] to [5], wherein the window film has infrared absorption properties.
[0025] (III) Beneficial effects
[0026] According to the present invention, it is possible to provide a window film having an adhesive layer capable of achieving both strong adhesiveness during attachment and removability after a predetermined period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1A 1 is a schematic cross-sectional view showing an example of the window film according to the present embodiment.
[0028] Figure 1B 1 is a schematic cross-sectional view showing another example of the window film according to the present embodiment. DETAILED DESCRIPTION
[0029] Hereinafter, the present invention will be described in detail based on specific embodiments.
[0030] (1. Window film)
[0031] like Figure 1A As shown, the window film 1 of this embodiment has a substrate 10 and an adhesive layer 11. In addition, as long as the effect of the present invention can be obtained, the window film may also have other components. That is, the window film may have layers other than the substrate and the adhesive layer. For example, in order to protect the adhesive layer 11 until it is attached to the adherend, a peeling sheet may be configured on the main surface 11a of the adhesive layer 11.
[0032] When the window film 1 is used, the exposed main surface 11 a of the pressure-sensitive adhesive layer 11 is attached to an adherend (mainly a window of a car or a building) to exhibit a predetermined function.
[0033] As described above, the window film is required to have both strong adhesion for exerting the anti-scattering function and re-peelability to suppress residual adhesive during peeling. However, if the adhesive layer of the window film is made to have strong adhesion, there will be the following problems: during the period from attachment to peeling, the adhesive force will increase with the environmental load, and the stronger the adhesion, the greater the load on the peeling of the window film, and it is easy to produce residual adhesive on the surface of the adherend.
[0034] Therefore, in this embodiment, the physical properties of the adhesive layer are controlled as follows, thereby achieving both strong adhesiveness during attachment and removability after a predetermined period of time. Components of the window film are described in detail below.
[0035] (1.1. Base material)
[0036] The substrate of this embodiment is a material that bears the rigidity of the window film and has the function of supporting the adhesive layer. As long as it has the above functions, the material of the substrate is not particularly limited. In this embodiment, a resin material is preferably used.
[0037] Examples of the resin material include: polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyolefin resins such as polyethylene, polypropylene, poly(4-methyl-1-pentene) and poly-1-butene; polyurethane resins; polycarbonate resins; polyvinyl chloride resins; polyether sulfone resins; polyethylene sulfide resins; styrene resins; acrylic resins; polyamide resins; and films formed from cellulose resins such as cellulose acetate or laminated films thereof.
[0038] Among them, films formed from polyolefin resins and polyester resins having excellent mechanical strength or economic efficiency or their laminated films are preferred. From the perspective of easily obtaining a window film satisfying the optical properties described later, films formed from polyester resins or their laminated films are particularly preferred. Among them, polyethylene terephthalate films or laminated films containing polyethylene terephthalate are preferred.
[0039] As the above-mentioned laminated film, it is preferred that a film is obtained by laminating multiple layers of one or more resin materials, and such a laminated film includes a multilayer structure having at least two nano-level layers, thereby also including a laminated film with wavelength selectivity, etc. In addition, as long as a window film that satisfies the optical properties described later can be obtained, a laminated film without wavelength selectivity or a laminated film with wavelength selectivity can be appropriately selected and used. The so-called wavelength selectivity here refers to the property of absorbing or reflecting a specific wavelength region, and a laminated film with wavelength selectivity refers to a laminated film that can control the transmittance of a specific wavelength region.
[0040] In order to improve the adhesion with the layer provided on the substrate, the surface treatment can be implemented on one side or both sides of the substrate by oxidation method or convexoconcave method. As the oxidation method, corona discharge treatment, chromic acid treatment (wet type), flame treatment, hot air treatment, ozone ultraviolet irradiation treatment, etc. can be illustrated. In addition, as the concaveoconcave method, sandblasting method, solvent treatment method, etc. can be illustrated.
[0041] As long as the specified rigidity is shown, the thickness of the substrate is not particularly limited and can be appropriately set according to the purpose of use. In the present embodiment, from the perspective of being able to guarantee the mechanical strength suitable for the workability during construction and the perspective of being easy to exert the above-mentioned adhesive properties, the thickness of the substrate is preferably 5 to 200 μm, more preferably 10 to 150 μm, and particularly preferably 15 to 100 μm. In addition, from the perspective of the design in which the optical properties described later are adjusted mainly with layers other than the substrate and the perspective of obtaining a thin window film, it is preferably 20 to 80 μm, and particularly preferably 25 to 60 μm.
[0042] The substrate may be transparent or colored. In addition, metals such as aluminum, gold, silver, copper, nickel, cobalt, chromium, tin, and indium may be deposited on the substrate.
[0043] (1.2. Adhesive layer)
[0044] The adhesive layer of the present embodiment is mainly attached to the surface of the window of a car or a building, thereby fixing the window film to the surface of the window, thereby exerting the prescribed function of the window film. The window to which the adhesive layer of the present embodiment is attached is preferably made of glass material. In addition, the surface of the window to which the adhesive layer of the present embodiment is attached can be the surface of the window on the incident side of direct sunlight, or the surface of the window on the opposite side. That is, if it is a car, it can be the surface of the window located outside the car, or the surface of the window located inside the car, and if it is a building, it can be the surface of the window located outside the house, or the surface of the window located inside the house. The adhesive layer 11 is preferably formed by an adhesive described later.
[0045] The adhesive layer may be composed of one layer (single layer) or two or more layers. When the adhesive layer has multiple layers, these multiple layers may be the same or different from each other, and the combination of layers constituting these multiple layers is not particularly limited.
[0046] The thickness of the adhesive layer 11 is preferably 1 to 100 μm, more preferably 3 to 70 μm, further preferably 5 to 50 μm, particularly preferably 7 to 35 μm, and preferably 10 to 25 μm or less. This makes it easier to exhibit appropriate adhesiveness and to achieve both strong adhesiveness and removability.
[0047] (1.2.1. Physical properties of adhesive)
[0048] In the present embodiment, by providing the adhesive with the following physical properties, it is possible to achieve both strong adhesion and removability of the window film.
[0049] (1.2.2. Initial Adhesion of Adhesive Layer)
[0050] In this embodiment, after being placed at 23°C and 50% relative humidity for 24 hours, the adhesive force when the adhesive layer attached to the float glass is peeled off from the float glass is preferably 1N / 25mm or more. This adhesive force is assumed to be the original adhesive force of attaching the window film to the adherend. In this embodiment, this adhesive force is set as the initial adhesive force.
[0051] By setting the initial adhesive force within the above range, the adhesion to the adherend (such as the surface of the window) becomes strong, and the window film can be stably fixed to the adherend (such as the surface of the window). As a result, the window film can exert a good anti-scattering function.
[0052] The initial adhesive force is preferably 1 to 100 N / 25 mm, more preferably 4 to 75 N / 25 mm, and further preferably 8 to 50 N / 25 mm. From the perspective of facilitating the adjustment of the heat-promoted adhesive force described later to the desired range or facilitating the adjustment of the wet heat-promoted adhesive force described later to the desired range, it is preferably 9 to 30 N / 25 mm, particularly preferably 10 to 20 N / 25 mm, and preferably 11 to 14 N / 25 mm. The specific measurement conditions of the initial adhesive force are described in the examples.
[0053] (1.2.3. Heat-promoted adhesion of adhesive layer)
[0054] In this embodiment, after being placed at 80°C for 168 hours, the adhesive layer attached to the float glass is preferably peeled off from the float glass with an adhesive force of 18N / 25mm or less. The adhesive force is the adhesive force over time after the window film is attached to the adherend and exposed to a high temperature environment, and is assumed to be the adhesive force that changes due to the environmental load before peeling after the window film is attached to the adherend. In this embodiment, the adhesive force is set as the heat-promoted adhesive force.
[0055] By setting the heat-promoted adhesive strength within the above range, after being attached to an adherend (such as a window surface), changes in adhesive strength (especially an increase in adhesive strength) due to environmental loads before peeling are suppressed. As a result, the re-peelability of the window film becomes good.
[0056] The heat-promoted adhesive force is preferably 1 to 18 N / 25 mm, more preferably 5 to 17.5 N / 25 mm, and even more preferably 10 to 17 N / 25 mm. Specific measurement conditions of the heat-promoted adhesive force are described in the Examples.
[0057] (1.2.4. Moisture-heat-promoted adhesion of adhesive layer)
[0058] In this embodiment, after being placed at 60°C and 95% relative humidity for 168 hours, the adhesive force when the adhesive layer attached to the float glass is peeled off from the float glass is preferably 22N / 25mm or less. The adhesive force is the adhesive force over time after the window film is attached to the adherend and exposed to a high temperature and high humidity environment. It is assumed that the adhesive force changes due to the environmental load before peeling after the window film is attached to the adherend. In this embodiment, the adhesive force is set as the wet heat-promoted adhesive force.
[0059] By setting the heat-moisture-accelerated adhesive strength within the above range, after being attached to an adherend (such as a window surface), changes in adhesive strength (especially an increase in adhesive strength) due to environmental loads before peeling can be suppressed. As a result, the re-peelability of the window film becomes good.
[0060] The heat-and-moisture accelerated adhesion is preferably 1 to 22 N / 25 mm, more preferably 4 to 20 N / 25 mm, and further preferably 8 to 18 N / 25 mm. From the perspective of both the initial adhesion and the heat-and-moisture accelerated adhesion, it is preferably 10 to 17 N / 25 mm, and particularly preferably 11 to 16 N / 25 mm. The specific measurement conditions of the heat-and-moisture accelerated adhesion are described in the Examples.
[0061] (1.2.5. Change ratio of storage modulus)
[0062] In this embodiment, the storage modulus (G') of the adhesive at 23°C and a frequency of 1 Hz 23 ) relative to the storage modulus (G') of the adhesive at 80°C and 1 Hz 80 ) ratio (G' 23 / G' 80 ) is preferably 3.5 or less. This ratio represents the change ratio of the storage modulus, and is an index showing to what extent the storage modulus at 80°C changes from the storage modulus at 23°C. By controlling the change ratio within the above range, there is a tendency that the change in the storage modulus accompanying the temperature change becomes smaller and the increase in the adhesive force over time is suppressed.
[0063] The change ratio of the storage modulus is preferably 1 to 3.5, more preferably 1.5 to 3.4, further preferably 2 to 3.3, and particularly preferably 2.5 to 3.2.
[0064] In addition, if the change ratio of the storage modulus is within the above range, there is no limit to the values of the storage modulus at 23°C and the storage modulus at 80°C. In the present embodiment, the storage modulus at 23°C is preferably 0.001 to 1 MPa, more preferably 0.01 to 0.6 MPa, and further preferably 0.03 to 0.3 MPa. From the perspective of easily adjusting the above-mentioned initial adhesion, heat-promoted adhesion, wet heat-promoted adhesion, etc. to the desired range, it is preferably 0.05 to 0.15 MPa, particularly preferably 0.07 to 0.11 MPa, among which 0.09 to 0.105 MPa is preferred. In addition, the storage modulus at 80°C is preferably 0.001 to 1 MPa, preferably 0.01 to 0.5 MPa, and more preferably 0.02 to 0.1 MPa. From the perspective of facilitating the adjustment of the above-mentioned initial adhesion, heat-promoted adhesion, and wet heat-promoted adhesion to the desired range, it is preferably 0.025 to 0.05 MPa, and preferably 0.03 to 0.034 MPa. If the storage modulus at 23°C and the storage modulus at 80°C are within the above range, it is easy to adjust the storage modulus change ratio within the above range, and it is easy to make the initial adhesion and re-peelability good.
[0065] The change ratio of the storage modulus can be adjusted by, for example, changing the composition, crosslinking structure, viscoelasticity, weight average molecular weight of the main polymer constituting the adhesive, glass transition temperature, and the like of the adhesive.
[0066] The storage modulus (G') can be measured using a known method. For example, the adhesive layer is made into a sample of a specified size, and a dynamic viscoelasticity measuring device is used to give strain to the sample within a specified temperature range and at a specified frequency to measure the elastic modulus. The storage modulus under the above conditions can be calculated from the measured elastic modulus.
[0067] (1.2.6. Gel fraction of adhesive)
[0068] The gel fraction of the adhesive of this embodiment is preferably 30 to 100%. This makes it easy to satisfy the above-mentioned change ratio of adhesive force and storage elastic modulus, and to achieve a good balance between initial adhesive force and removability.
[0069] The gel fraction of the adhesive of this embodiment is more preferably 40 to 95%, further preferably 50 to 90%, particularly preferably 60 to 80%, and from the perspective of facilitating adjustment of the initial adhesion, heat-promoted adhesion, wet heat-promoted adhesion, etc. to the desired range, preferably 63 to 75%, and preferably 65 to 71%. The gel fraction of the adhesive can be measured by the method shown in the test examples described later.
[0070] (1.3. Composition of adhesive)
[0071] As long as the adhesive of the present embodiment has the above-mentioned physical properties, the composition of the adhesive is not particularly limited. For example, it can be any one of acrylic adhesive, polyester adhesive, polyurethane adhesive, rubber adhesive, silicone adhesive, etc. In addition, the adhesive can be any one of emulsion type, solvent type or solvent-free type. In addition, the adhesive can have a cross-linked structure or not.
[0072] The adhesive of this embodiment is preferably an acrylic adhesive, and more preferably an acrylic adhesive having a cross-linked structure, from the viewpoint of easily achieving the above-mentioned physical properties and from the viewpoint of adhesive physical properties, optical characteristics, and the like.
[0073] Specifically, the adhesive is preferably an adhesive obtained from an adhesive composition containing a (meth)acrylate polymer (A) (hereinafter sometimes referred to as "adhesive composition P"), preferably an adhesive obtained by cross-linking an adhesive composition containing a (meth)acrylate polymer (A) and a cross-linking agent (B), that is, an adhesive containing a cross-linked product of a (meth)acrylate polymer (A) and a cross-linking agent (B). If it is this adhesive, it is easy to satisfy the above-mentioned physical properties. In addition, in this specification, (meth)acrylic acid refers to both acrylic acid and methacrylic acid. Other similar terms are also the same. In addition, the concept of "copolymer" is also included in "polymer".
[0074] (1.3.1. (Meth)acrylate polymer (A))
[0075] The (meth)acrylate polymer (A) preferably contains, as monomer units constituting the polymer, an alkyl (meth)acrylate and a monomer having a reactive functional group in the molecule (reactive functional group-containing monomer).
[0076] By containing the (meth)acrylic acid alkyl ester, the adhesive can exhibit good adhesiveness. As the (meth)acrylic acid alkyl ester, those having an alkyl group with carbon atoms of 1 to 20 are preferred. The alkyl group may be linear or branched, or may have a cyclic structure.
[0077] Examples of the (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, and octadecyl (meth)acrylate.
[0078] Among them, from the perspective of adhesion and the change ratio of storage modulus, alkyl (meth)acrylates having an alkyl group with 1 to 8 carbon atoms are preferred. Specifically, n-butyl (meth)acrylate and isobutyl (meth)acrylate are preferred, and n-butyl acrylate and isobutyl acrylate are more preferred. In addition, they may be used alone or in combination.
[0079] The (meth)acrylate polymer (A) preferably contains 50 to 99.9% by mass of an alkyl (meth)acrylate having an alkyl carbon number of 1 to 20 as a monomer unit constituting the polymer, more preferably 60 to 99% by mass, further preferably 70 to 95% by mass, and particularly preferably 80 to 90% by mass. Thus, the resulting adhesive is easy to exert appropriate adhesion and is easy to adjust the change ratio of the storage modulus to the above range. In addition, other monomer components of a desired amount can be introduced into the (meth)acrylate polymer (A).
[0080] By containing a monomer containing a reactive functional group, the (meth)acrylate polymer (A) reacts with the crosslinking agent (B) described later via the reactive functional group from the monomer containing a reactive functional group, and a crosslinking structure (three-dimensional network structure) is formed in the adhesive, thereby obtaining an adhesive having a desired cohesive force. Thus, the adhesive easily satisfies the above-mentioned physical properties related to adhesive force.
[0081] As the monomer containing reactive functional groups, preferably monomers containing hydroxyl groups in the molecule (hydroxyl-containing monomers), monomers containing carboxyl groups in the molecule (carboxyl-containing monomers), monomers containing amino groups in the molecule (amino-containing monomers), etc. can be listed. These monomers containing reactive functional groups can be used alone or in combination. Among them, preferably hydroxyl-containing monomers or carboxyl-containing monomers. Thus, it is easy to form a cross-linked structure via a cross-linking agent (B), which is easy to satisfy the above-mentioned physical properties related to adhesion.
[0082] As hydroxyl-containing monomers, examples include (meth) 2-hydroxyethyl acrylate, (meth) 2-hydroxypropyl acrylate, (meth) 3-hydroxypropyl acrylate, (meth) 2-hydroxybutyl acrylate, (meth) 3-hydroxybutyl acrylate, (meth) 4-hydroxybutyl acrylate, and (meth) hydroxyalkyl acrylates such as acrylates. Among them, from the perspective of easily achieving the above-mentioned physical properties related to adhesion, (meth) hydroxyalkyl acrylates having a hydroxyalkyl group with a carbon number of 1 to 4 are preferably used. Specifically, for example, (meth) 2-hydroxyethyl acrylate or (meth) 4-hydroxybutyl acrylate can be preferably listed, (meth) 2-hydroxyethyl acrylate can be more preferably listed, and methacrylate 2-hydroxyethyl acrylate can be particularly preferably listed. They can be used alone or in combination of two or more.
[0083] Examples of carboxyl group-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Of these, acrylic acid or methacrylic acid is preferred, and methacrylic acid is particularly preferred, from the perspective of the reactivity of the carboxyl group in the obtained (meth)acrylate polymer (A) with a crosslinking agent and copolymerizability with other monomers. These may be used alone or in combination of two or more.
[0084] The (meth)acrylate polymer (A) preferably contains 1 to 30% by mass of a reactive functional group-containing monomer as a monomer unit constituting the polymer, more preferably 2 to 20% by mass, further preferably 4 to 15% by mass, and particularly preferably 6 to 10% by mass. As a result, the cohesive force of the adhesive obtained by the crosslinking reaction with the crosslinking agent (B) becomes moderate, and the above-mentioned physical properties related to adhesive force are easily satisfied.
[0085] When the (meth)acrylate polymer (A) contains both a hydroxyl-containing monomer and a carboxyl-containing monomer as the reactive functional group-containing monomer, the (meth)acrylate polymer (A) preferably contains 1 to 30% by mass of a hydroxyl-containing monomer as a monomer unit constituting the polymer, more preferably 2 to 20% by mass, further preferably 4 to 15% by mass, and particularly preferably 6 to 10% by mass. In addition, it is preferred to contain 0.01 to 1% by mass of a carboxyl-containing monomer, more preferably 0.05 to 0.8% by mass, further preferably 0.1 to 0.6% by mass, and particularly preferably 0.15 to 0.3% by mass. By containing the hydroxyl-containing monomer and the carboxyl-containing monomer in the above range, the desired cohesive force is exerted by good cross-linking reactivity with the cross-linking agent, and it is easy to obtain an adhesive having the desired adhesive properties.
[0086] (Meth) acrylate polymer (A) also preferably does not contain carboxyl-containing monomers as monomer units constituting the polymer. By not containing carboxyl-containing monomers, it is easy to suppress the rise of the adhesive force to the adherend (e.g., glass) over time, and it is easy to suppress the generation of residual glue during peeling. Since the carboxyl group is an acid component, even if there is a material that produces a bad condition due to acid on the attached object, such as a transparent conductive film or a metal film, a metal mesh, etc. such as tin-doped indium oxide (ITO), the above-mentioned bad condition (corrosion, resistance value change, etc.) caused by acid can be suppressed.
[0087] Here, "does not contain a carboxyl group-containing monomer" means that it does not contain a carboxyl group-containing monomer substantially. In addition to not containing a carboxyl group-containing monomer at all, it is also allowed to contain a carboxyl group-containing monomer to the extent that corrosion of the transparent conductive film or metal wiring caused by the carboxyl group does not occur. Specifically, in the (meth)acrylate polymer (A), as a monomer unit, it is allowed to contain a carboxyl group-containing monomer in an amount of 0.01% by mass or less, preferably in an amount of 0.001% by mass or less.
[0088] In the present embodiment, the (meth)acrylate polymer (A) preferably contains a monomer that does not contain a reactive functional group as a monomer unit constituting the polymer. This is because the above-mentioned effect of the monomer containing a reactive functional group will not be hindered. As such a monomer, non-reactive nitrogen atom-containing monomers such as N-vinyl-2-pyrrolidone, (meth)acrylate methoxyethyl, (meth)acrylate ethoxyethyl (meth)acrylate and other (meth)acrylate alkoxyalkyl esters, vinyl acetate, styrene, etc. can be exemplified. Among them, from the perspective that the resulting adhesive is easy to exert the desired adhesion, it is preferably containing vinyl acetate. They can be used alone or in combination of two or more.
[0089] The (meth)acrylate polymer (A) preferably contains 1 to 15% by mass of a monomer having no reactive functional group as a monomer unit constituting the polymer, more preferably 2 to 10% by mass, and further preferably 3 to 8% by mass. This makes it easier to satisfy the above-mentioned physical properties related to adhesiveness.
[0090] The (meth)acrylate polymer (A) may be polymerized in the form of a random copolymer or a block copolymer.
[0091] The weight average molecular weight of the (meth)acrylate polymer (A) is preferably 200,000 to 2,000,000, more preferably 300,000 to 1,400,000, further preferably 400,000 to 1,100,000, particularly preferably 450,000 to 900,000, and preferably 500,000 to 800,000. Thus, it is easy to satisfy the above-mentioned physical properties related to adhesion. In addition, the weight average molecular weight in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC).
[0092] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.
[0093] (1.3.2. Cross-linking agent (B))
[0094] The crosslinking agent (B) of this embodiment crosslinks the (meth)acrylate polymer (A) to form a crosslinked structure (three-dimensional network structure) by heating the adhesive composition P containing the crosslinking agent (B). As a result, the cohesive force of the obtained adhesive is improved, the initial adhesive force of the adhesive layer can be improved, and the increase in the adhesive force over time after attachment can be suppressed. Therefore, the re-peelability of the obtained window film can be improved.
[0095] As the above-mentioned crosslinking agent (B), it is sufficient to react with the reactive group possessed by the (meth) acrylate polymer (A). For example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. can be illustrated. Among them, from the perspective of crosslinking with the (meth) acrylate polymer (A), isocyanate crosslinking agents or epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are particularly preferred. In addition, the crosslinking agent (B) can be used alone or in combination of two or more.
[0096] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate; and their biuret bodies and isocyanurate bodies; and adducts as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among them, from the perspective of reactivity with hydroxyl groups, the biuret body of aliphatic polyisocyanates is more preferred, and the biuret body of hexamethylene diisocyanate is particularly preferred.
[0097] The content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, particularly preferably 0.15 to 1 part by mass, further preferably 0.2 to 0.7 parts by mass, and particularly preferably 0.25 to 0.5 parts by mass, relative to 100 parts by mass of the (meth)acrylate polymer (A). This makes it easy to satisfy the above-mentioned physical properties related to adhesion and the physical properties of the change ratio of the storage modulus.
[0098] (1.3.3. Ultraviolet absorber (C))
[0099] In order to impart the ultraviolet shielding function to the window film, the adhesive of this embodiment preferably contains an ultraviolet absorber, and more preferably contains an ultraviolet absorber with excellent ultraviolet absorbency that can adjust the ultraviolet transmittance described later to a desired range. Therefore, the window film of this embodiment exhibits good ultraviolet absorbency regardless of whether the surface of the window on the side directly receiving sunlight is the attachment surface or the surface of the window on the opposite side is the attachment surface.
[0100] As the ultraviolet absorber, for example, compounds of benzophenone series, benzotriazole series, benzoate series, benzoxazinone series, methine series, triazine series, phenyl salicylate series, cyanoacrylate series, nickel complex salt series, etc. can be listed, and one type can be used alone, or two or more types can be used in combination. Among the above ultraviolet absorbers (C), benzophenone series, benzotriazole series, and triazine series compounds are preferably used, and benzophenone series and triazine series compounds are more preferably used.
[0101] Examples of the benzophenone-based compound include 2,2′-dihydroxy-4-methoxybenzophenone, 2,2′-dihydroxy-4,4′-dimethoxybenzophenone, 2,2′,4,4′-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, and 2-hydroxy-4-octyloxybenzophenone.
[0102] Examples of the triazine compound include 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris[2-hydroxy-4-(3-butoxy-2-hydroxypropoxy)phenyl]-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine.
[0103] Examples of benzotriazole compounds include 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-amyl-5'-isobutylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-isobutyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-isobutyl-5'-propylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and 2-[2'-hydroxy-5'-(1,1,3,3-tetramethyl)phenyl]benzotriazole.
[0104] The content of the ultraviolet absorber (C) in the adhesive composition P is preferably 0.1 to 25 parts by mass, more preferably 0.5 to 18 parts by mass, further preferably 1 to 12 parts by mass, and particularly preferably 4 to 10 parts by mass relative to 100 parts by mass of the (meth)acrylate polymer (A). Thus, the obtained adhesive layer can exert excellent ultraviolet shielding properties. In addition, it is easy to obtain a window film that satisfies the optical properties such as ultraviolet transmittance described later.
[0105] (1.3.4. Cross-linking accelerator (D))
[0106] In order to promote the crosslinking of the (meth)acrylate polymer (A), the adhesive of the present embodiment preferably contains a catalyst as a crosslinking accelerator. By containing a crosslinking accelerator, the cohesive force of the adhesive is improved. As a result, the initial adhesion of the adhesive layer can be improved, and the increase in adhesion over time after attachment can be suppressed. Therefore, the re-peelability of the window film can be improved.
[0107] Examples of crosslinking accelerators include compounds of heavy metals such as tin, zinc, lead, mercury, and bismuth (including organometallic compounds); complexes of transition metals such as titanium, iron, copper, zirconium, nickel, cobalt, and manganese, especially acetylacetonate complexes; amine compounds; acid catalysts such as p-toluenesulfonic acid, phosphoric acid, hydrochloric acid, and ammonium chloride. Among them, organotin compounds and amine compounds are preferred from the perspective of promoting the crosslinking reaction, and organotin compounds are particularly preferred. In addition, the crosslinking accelerator may be used alone or in combination of two or more.
[0108] Examples of the organotin compound include: organotin compounds such as dimethyltin dichloride; fatty acid salts of organotin compounds such as dimethyltin dilaurate, dimethyltin di(2-ethylhexanoate), dimethyltin diacetate, dibutyltin dilaurate, dihexyltin diacetate, and dioctyltin dilaurate; thioglycolate salts of organotin compounds such as dimethyltin bis(isooctylthioglycolate) salt and dioctyltin bis(isooctylthioglycolate) salt; metal soaps such as tin octoate and tin decanoate, etc. Among the above, fatty acid salts of organotin compounds are preferred from the viewpoint of promoting the crosslinking reaction, and dibutyltin dilaurate is particularly preferred.
[0109] The content of the crosslinking accelerator (D) in the adhesive composition P is preferably 0.001 to 1 part by mass, more preferably 0.002 to 0.5 part by mass, and even more preferably 0.003 to 0.1 part by mass relative to 100 parts by mass of the (meth)acrylate polymer (A). This makes it easier to achieve both initial adhesive strength and removability of the adhesive layer.
[0110] (1.3.5. Other additives)
[0111] As required, adhesive composition P also can contain the additive that is usually used in acrylic adhesive.As such additive, can illustrate tackifier, filler, softener, antioxidant, light stabilizer, crosslinking agent, coloring agent, modifier, rust inhibitor, flame retardant, anti-hydrolysis agent, surface lubricant, corrosion inhibitor, heat stabilizer, lubricant, antistatic agent, inhibitor, catalyst, leveling agent, thickener, dispersant, defoamer, surfactant etc.In addition, the polymerization solvent or diluting solvent described later are not included in the additive that constitutes adhesive composition P.
[0112] In addition, in this embodiment, it is preferred not to use a silane coupling agent as an additive, that is, the adhesive of this embodiment preferably does not contain a silane coupling agent. This is because if a silane coupling agent is used, the silanol group generated by hydrolysis reacts with Si-OH present on the glass surface to form a covalent bond through a condensation reaction, especially under hot and humid conditions, which tends to increase the adhesion.
[0113] Here, "containing no silane coupling agent" means substantially containing no silane coupling agent, and in addition to not containing any silane coupling agent at all, it is allowed to contain a silane coupling agent to such an extent that the adhesive force due to the silane coupling agent does not increase. Specifically, the adhesive composition P is allowed to contain a silane coupling agent in an amount of 0.01% by mass or less, preferably 0.001% by mass or less.
[0114] (1.4. Hard coating)
[0115] In addition to the substrate and the adhesive layer, the window film of this embodiment may also have a hard coating layer. Figure 1B As shown, when the window film of this embodiment has a hard coat layer, the hard coat layer 12 is preferably disposed on the main surface 10b opposite to the main surface 10a on which the adhesive layer 11 is disposed in the substrate 10. Furthermore, the hard coat layer is preferably disposed between the substrate 10 and the adhesive layer 11.
[0116] The hard coating layer is made of a material that is superior to the base material in hardness, scratch resistance, weather resistance, etc. In addition, since the adhesive layer of the window film is attached to the adherend, the hard coating layer is exposed to the outside in the window film. Therefore, after construction, even if any force is applied from the outside, it is difficult for the external force to be directly transmitted to the adhesive layer and the adherend (windows of cars, buildings, etc.), so that excellent impact resistance can be exerted. Furthermore, even if the adherend is damaged, its fragments can be suppressed from scattering, so excellent anti-scattering properties can be exerted. Therefore, the appearance of mobile bodies such as cars and buildings can be maintained, and safety can be improved at the same time.
[0117] From the viewpoint of the surface hardness, scratch resistance and weather resistance of the window film, the thickness of the hard coat layer is preferably 0.5 to 20 μm, more preferably 1 to 15 μm, particularly preferably 1.5 to 10 μm, and particularly preferably 2 to 6 μm.
[0118] The material constituting the hard coat layer is not particularly limited as long as it is a material superior to the substrate in hardness, scratch resistance, weather resistance, etc. The hard coat layer of this embodiment is preferably a cured product of a hard coat layer-forming composition containing an energy-ray-curable resin.
[0119] (1.4.1. Composition for forming hard coat layer)
[0120] In this embodiment, the hard coat forming composition Q can be composed of a thermosetting material or an energy-ray-curing material. From the perspective of productivity and the ease of obtaining the desired scratch resistance, it is preferably composed of an energy-ray-curing material, more preferably contains an energy-ray-curing resin (a), and further preferably contains an energy-ray-curing resin (a) and a photopolymerization initiator (b).
[0121] (1.4.2. Energy-beam curable resin (a))
[0122] The energy-ray-curable resin is not particularly limited, and any conventionally known energy-ray-curable resin can be selected, for example, an energy-ray-curable monomer, oligomer, or a composition containing these.
[0123] Examples of the energy-beam-curable monomer include polyfunctional (meth)acrylates, and examples of the energy-beam-curable oligomer include urethane (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, and silicone (meth)acrylates.
[0124] Examples of the polyfunctional (meth)acrylate include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate and other pentaerythritol polyfunctional (meth)acrylates, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate and other dipentaerythritol polyfunctional (meth)acrylates, glycerol tri(meth)acrylate, triallyl (meth)acrylate and the like.
[0125] Among them, pentaerythritol polyfunctional (meth)acrylate or dipentaerythritol polyfunctional (meth)acrylate is preferred from the viewpoint of being able to impart appropriate hardness, scratch resistance, weather resistance, and the like to the hard coat layer.
[0126] (1.4.3. Photopolymerization initiator (b))
[0127] When ultraviolet rays are used as energy rays for curing the hard coat layer forming composition Q, it is preferred that the hard coat layer forming composition Q contains a photopolymerization initiator (b). By containing a photopolymerization initiator, a hard coat layer can be effectively formed when ultraviolet rays are irradiated to the hard coat layer forming composition Q. Here, the photopolymerization initiator refers to a compound that generates free radical species by irradiation with active energy rays such as ultraviolet rays.
[0128] Examples of the photopolymerization initiator include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinoacetone-1-one. , 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzil dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo[2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane-1-one], etc. One of them may be used alone, or two or more thereof may be used in combination.
[0129] The content of the photopolymerization initiator (b) is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 3 to 10 parts by mass relative to 100 parts by mass of the energy-ray-curable resin (a). Thus, the obtained hard coating layer can easily exhibit the desired surface hardness and scratch resistance.
[0130] (1.4.4. Infrared absorber (c))
[0131] In order to impart heat shielding properties to the window film, the hard coat layer-forming composition Q of the present embodiment preferably further contains an infrared absorber (c). The infrared absorber (c) is preferably an infrared absorber having excellent near-infrared absorption properties.
[0132] Examples of the infrared absorber (c) include organic infrared absorbers and inorganic infrared absorbers.
[0133] As organic infrared absorbers, there can be listed cyanine compounds, squarylium compounds, nickel thiolate complex compounds, naphthalocyanine compounds, phthalocyanine compounds, triarylmethane compounds, naphthoquinone compounds, anthraquinone compounds; and amino compounds such as perchlorate of N,N,N',N'-tetrakis (p-di-n-butylaminophenyl)-p-phenylenediammonium, chloride of phenylenediammonium, hexafluoroantimonate of phenylenediammonium, fluoroborate of phenylenediammonium, fluoride of phenylenediammonium, and perchlorate of phenylenediammonium; phosphate copper compounds obtained by reaction of copper compounds and dithiourea compounds, phosphorus compounds and copper compounds, phosphate compounds and copper compounds, etc. It can be appropriately selected according to weather resistance and the optical properties sought.
[0134] Examples of the inorganic infrared absorber include titanium oxide, zirconium oxide, tantalum oxide, niobium oxide, zinc oxide, indium oxide, tin-doped indium oxide (ITO), tin oxide, antimony-doped tin oxide (ATO), zinc antimonate, cesium oxide, zinc sulfide, hexaboride (LaB 6 , CeB 6 , PrB 6 、NdB 6 , GdB 6 , TbB 6 , DyB 6 、HoB 6 , YB 6 、SmB 6 ,EuB 6 , ErB 6 、TmB 6 , YbB 6 , LuB 6 , SrB 6 , CaB 6 etc.), tungsten oxide compounds, etc. Among them, tungsten oxide compounds, tin-doped indium oxide (ITO), and antimony-doped tin oxide (ATO) are preferred.
[0135] The content of the infrared absorber (c) in the hard coat layer forming composition Q is preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, relative to 100 parts by mass of the energy ray curable resin (a). This can provide a window film that satisfies optical properties such as near infrared transmittance described below.
[0136] In addition, in this embodiment, from the perspective of the scratch resistance of the window film, it is also preferred that the hard coat layer does not contain an infrared absorber. By not containing an infrared absorber, the content ratio of the active energy ray curing resin in the hard coat layer can be increased, or a material that can improve the scratch resistance can be added separately, so it is easy to design to improve the scratch resistance and surface hardness.
[0137] Here, "does not contain an infrared absorber" means that the infrared absorber is substantially not contained. In addition to not containing an infrared absorber at all, it is allowed to contain an infrared absorber to an extent that does not cause an increase in adhesive force due to the infrared absorber. Specifically, in the hard coat layer forming composition Q, it is allowed to contain an infrared absorber in an amount of 0.1% by mass or less, preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.
[0138] (1.4.5. Leveling agent (d))
[0139] From the perspective of the weather resistance and antifouling properties of the window film, the hard coating forming composition Q of the present embodiment preferably contains a leveling agent (d). As the leveling agent, for example, silicone leveling agents, fluorine leveling agents, acrylic leveling agents, vinyl leveling agents, etc. can be listed. Among them, from the perspective of the above-mentioned effects, silicone leveling agents are preferred, and silicone leveling agents with cyclic siloxane structures are more preferred. In addition, the leveling agent can be used alone or in combination of two or more.
[0140] The content of the leveling agent (d) in the hard coat layer forming composition Q is preferably 0.001 to 1 part by mass, more preferably 0.01 to 0.5 parts by mass, further preferably 0.02 to 0.1 parts by mass, and particularly preferably 0.04 to 0.08 parts by mass, relative to 100 parts by mass of the energy-ray-curable resin (a). Thus, the weather resistance and antifouling properties of the window film are improved without hindering the optical properties described later.
[0141] (1.4.6. Other additives)
[0142] In addition, other additives can be appropriately included within the scope of not damaging the effect of the present invention. As other additives, for example, antioxidants, ultraviolet absorbers, antistatic agents, colorants, polymerization accelerators, polymerization inhibitors, plasticizers, antiviral agents, antibacterial agents, fillers and diluents can be listed.
[0143] (1.5. Physical properties of window films)
[0144] The window film of this embodiment preferably has the following physical properties.
[0145] The light transmittance (ultraviolet transmittance) of the window film of this embodiment in the wavelength range of 300 to 380 nm is preferably 10% or less. Thus, the window film has a good ultraviolet shielding function, which can inhibit the deterioration of the components inside the building or car, and can also prevent the skin of people inside the building or car from being rough or sunburned.
[0146] From the above perspectives, the ultraviolet transmittance is preferably 5% or less, more preferably 1% or less, and most preferably 0%. The lower limit of the ultraviolet transmittance is usually 0% or more.
[0147] The light transmittance (visible light transmittance) of the window film of this embodiment in the wavelength range of 380 to 780 nm is preferably 98% or less, more preferably 95% or less. Thus, the existence of the window can be identified. For example, although the visibility of window glass with high transparency is very excellent, there is a risk of collision and breakage without noticing the existence of the window. Therefore, from the perspective of safety, it is preferred to have high transparency and be able to identify the existence of the window at the same time. On the other hand, in the case where visibility across the window is required, from the perspective of improving visibility, the visible light transmittance is preferably 10% or more, more preferably 30% or more, further preferably 50% or more, particularly preferably 70% or more, wherein preferably 80% or more, and most preferably 90% or more. Thus, for the windows of buildings, the scenery across the windows can be well viewed, and for the windows of cars, the situation outside the car can be well identified, thereby improving safety during driving.
[0148] The light transmittance (near infrared transmittance) of the window film of this embodiment in the wavelength range of 780 to 2500 nm is preferably 90% or less. Thus, the window film exhibits good infrared heat insulation performance, can suppress the increase in the surface temperature of the internal components or people of a building or a car, and can also suppress the temperature increase of the internal space.
[0149] From the above perspective, the near infrared transmittance is preferably 70% or less, preferably 50% or less, more preferably 40% or less, and further preferably 30% or less. The lower limit of the near infrared transmittance is usually 0%, and from the perspective of taking into account the visible light transmittance, it is sometimes preferably 10% or more, more preferably 20% or more, and further preferably 30% or more.
[0150] The ultraviolet light transmittance, visible light transmittance, and near infrared light transmittance of the window film can be measured by the method described in the test examples described later.
[0151] The total thickness of the window film of this embodiment is preferably 5 to 200 μm, more preferably 10 to 160 μm, particularly preferably 20 to 140 μm, preferably 40 to 120 μm, further preferably 50 to 100 μm, and particularly preferably 60 to 80 μm. This improves the handleability of the window film and facilitates the desired adhesive properties.
[0152] (1.6. Preparation of adhesive composition)
[0153] The adhesive composition P can be prepared, for example, by first preparing a (meth)acrylate polymer (A) and mixing the obtained (meth)acrylate polymer (A) with a crosslinking agent (B). Additives may be added as needed.
[0154] The (meth)acrylate polymer (A) can be prepared, for example, by polymerizing a mixture of monomers constituting the polymer by a common radical polymerization method. The polymerization of the (meth)acrylate polymer (A) can be carried out by a solution polymerization method using a polymerization initiator as required.
[0155] As the polymerization solvent used in the solution polymerization method, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc. can be exemplified. One polymerization solvent can be used, or two or more can be used simultaneously. In addition, as the polymerization initiator, azo compounds, organic peroxides, etc. can be listed, and two or more can also be used simultaneously. In addition, in the above-mentioned polymerization step, by blending a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.
[0156] Next, a crosslinking agent (B) and, if necessary, an ultraviolet absorber (C), a crosslinking accelerator (D), a diluting solvent, etc. are added to the obtained solution of the (meth)acrylate polymer (A), and the mixture is thoroughly mixed to obtain an adhesive composition P (coating solution) diluted with a solvent. Additives may also be added as necessary.
[0157] In addition, when any of the above-mentioned components is a solid component, or when any of the above-mentioned components is a component that precipitates when mixed with other components in an undiluted state, the component can also be dissolved or diluted in a diluting solvent in advance and then mixed with other components.
[0158] Examples of the diluting solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as dichloromethane and ethylene chloride, alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol, ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, and cellosolve-based solvents such as ethyl cellosolve.
[0159] As the concentration and viscosity of the prepared coating solution, as long as it is a range that can be applied, it can be appropriately selected according to the situation. For example, the concentration of the adhesive composition P is diluted to 10~60 mass %. In addition, when obtaining the coating solution, the addition of a diluting solvent, etc. is not a necessary condition, as long as the adhesive composition P is a viscosity that can be applied, etc., then no diluting solvent may be added. In this case, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth) acrylate polymer (A) is directly used as a diluting solvent.
[0160] (1.7. Manufacture of adhesive)
[0161] The adhesive constituting the adhesive layer is preferably obtained by crosslinking the above-mentioned adhesive composition P. The crosslinking of the adhesive composition P can usually be carried out by heat treatment. In addition, the drying process when the diluting solvent or the like is volatilized from the coating film of the adhesive composition P applied on the desired object can also be used as the heat treatment.
[0162] The heating temperature of the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes.
[0163] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23°C, relative humidity 50%) as required. If aging is required, an adhesive having a cross-linked structure is obtained after the aging period. If aging is not required, an adhesive having a cross-linked structure is obtained after the heat treatment is completed.
[0164] (1.8. Manufacturing of window films)
[0165] There is no particular limitation on the method for manufacturing the window film, and the window film can be manufactured by a known method. For example, a coating liquid of the adhesive composition P is applied to one main surface of the substrate and heat-treated to crosslink the adhesive composition P, thereby forming a coating layer with a predetermined thickness, and the release surface of the release sheet is superimposed on the coating layer. Alternatively, a coating liquid of the adhesive composition P is applied to the release surface of the release sheet and heat-treated to crosslink the adhesive composition P, thereby forming a coating layer with a predetermined thickness, and one main surface of the substrate is superimposed on the coating layer.
[0166] When aging is required, the coating layer becomes the adhesive layer after a predetermined aging period. When aging is not required, the coating layer directly becomes the adhesive layer. Thus, a window film can be obtained.
[0167] When the window film has a hard coating layer, it is preferred that the hard coating layer is formed on the other main surface of the substrate before the adhesive layer is formed on one main surface of the substrate. At this time, the coating liquid of the hard coating layer forming composition Q is first applied to the other main surface of the substrate and dried. After drying, the hard coating layer forming composition Q after the solvent is evaporated is irradiated with active energy rays such as ultraviolet rays and electron beams to be cured, thereby forming a hard coating layer on the substrate.
[0168] When ultraviolet rays are irradiated as active energy rays, a known device such as a high-pressure mercury lamp, a xenon lamp, or a metal halide lamp can be used as an ultraviolet irradiation device.
[0169] Examples of a method for applying the coating solution of the adhesive composition P and the hard coat layer-forming composition include a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, and a gravure coating method.
[0170] In addition, unless otherwise specified, in this specification, when "X to Y" (X and Y are arbitrary numbers) is recorded, it means "X or more and Y or less", and also includes the meaning of "preferably greater than X" or "preferably less than Y". In addition, unless otherwise specified, when "X or more" (X is an arbitrary number) is recorded, it means "preferably greater than X", and unless otherwise specified, when "Y or less" (Y is an arbitrary number) is recorded, it means "preferably less than Y".
[0171] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment at all, It can change in various forms within the scope of this invention.
[0172] Example
[0173] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.
[0174] (Example 1)
[0175] 1. Preparation of (meth)acrylate polymer (A)
[0176] 44 parts by mass of n-butyl acrylate, 44 parts by mass of isobutyl acrylate, 5 parts by mass of vinyl acetate and 7 parts by mass of 2-hydroxyethyl methacrylate were copolymerized to prepare a (meth)acrylate polymer (A). The molecular weight of the obtained (meth)acrylate polymer (A) was measured by the method shown below, and the weight average molecular weight (Mw) was 700,000.
[0177] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured using gel permeation chromatography (GPC) under the following conditions (GPC measurement).
[0178] (Measurement conditions)
[0179] ·GPC measuring apparatus: HLC-8020 manufactured by TOSOH CORPORATION
[0180] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION
[0181] TSK guard column HXL-H
[0182] TSK gel GMHXL (×2)
[0183] TSK gel G2000HXL
[0184] ·Test solvent: tetrahydrofuran
[0185] ·Measurement temperature: 40℃
[0186] 2. Preparation of adhesive composition
[0187] 100 parts by mass (solid content conversion value; the same applies hereinafter) of the (meth)acrylate polymer (A) obtained in the above step 1, 0.35 parts by mass of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "TAKENATE D-165N") (B1) as a crosslinking agent (B), 5 parts by mass of a benzophenone ultraviolet absorber (manufactured by Solvay Japan, product name "CYASORB UV-24") (C1) as an ultraviolet absorber (C), and 0.005 parts by mass of dibutyltin dilaurate (D1) as a crosslinking accelerator (D) were mixed, stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition having a solid content concentration of 30% by mass.
[0188] 3. Preparation of hard coat layer forming composition
[0189] 50 parts by mass of dipentaerythritol pentaacrylate as an energy-ray-curable resin (a), 50 parts by mass of dipentaerythritol hexaacrylate as an energy-ray-curable resin (a), 5.0 parts by mass of 2-methyl-[4-(methylthio)phenyl]-2-morpholinyl-1-propane as a photopolymerization initiator (b), and 0.05 parts by mass of octamethylcyclotetrasiloxane as a leveling agent (d) were mixed, stirred sufficiently, and diluted with propylene glycol monomethyl ether to obtain a coating solution of a hard coat layer-forming composition having a solid content concentration of 30% by mass.
[0190] 4. Manufacturing of window films
[0191] A polyethylene terephthalate (PET) film with a thickness of 50 μm was prepared as a substrate. The coating solution of the hard coat layer forming composition prepared in the above step 3 was applied to one main surface of the PET film by gravure coating so that the thickness after drying was 3 μm, and heated at 70°C for 1 minute to fully remove the diluent solvent. Then, in a nitrogen atmosphere, ultraviolet rays were irradiated using an ultraviolet irradiation device (manufactured by GS Yuasa International Ltd., product name "Nitrogen Purge Small Conveyor Type UV Irradiation Device CSN2-40") under the following conditions to cure the hard coat layer forming composition, form a hard coat layer (thickness: 3 μm), and obtain a PET film with a hard coat layer.
[0192] [Ultraviolet irradiation conditions]
[0193] Light source: high pressure mercury lamp
[0194] Lamp power: 1.4kW
[0195] Conveyor speed: 1.2m / min
[0196] Illuminance: 120mW / cm 2
[0197] Light intensity: 240mJ / cm 2
[0198] Next, the coating solution of the adhesive composition prepared in the above step 2 was applied to the release-treated surface of a release sheet (manufactured by LINTEC Corporation, product name "SP-PET381031") after a single side of a polyethylene terephthalate film was subjected to release treatment with a silicone-based release agent by die coating, so that the thickness after drying was 20 μm. Then, the film was heated at 90° C. for 1 minute to fully remove the diluent solvent, thereby forming an adhesive layer and obtaining a laminate of the release sheet and the adhesive layer. The adhesive layer of the laminate was bonded to the main surface of the PET film with a hard coating layer on the side where the hard coating layer was not formed in a contacting manner to obtain a window film.
[0199] (Examples 2 to 6, Comparative Examples 1 to 4)
[0200] A window film was manufactured by the same method as in Example 1, except that the composition of the (meth)acrylate polymer (A) constituting the adhesive layer, the blending amount of the crosslinking agent (B), the type of the ultraviolet absorber (C), the blending amount of the crosslinking accelerator (D), the blending amount of the silane coupling agent, and the type and blending amount of the infrared absorber (c) added to the hard coat layer were changed as shown in Table 1.
[0201] [Table 1]
[0202]
[0203] Details of the abbreviations and the like described in Table 1 are as follows.
[0204] [Hard coating]
[0205] (Curing resin (a))
[0206] DPPA: Dipentaerythritol pentaacrylate
[0207] DPHA: Dipentaerythritol hexaacrylate
[0208] (Photopolymerization initiator (b))
[0209] b1: 2-methyl-[4-(methylthio)phenyl]-2-morpholinyl-1-propane
[0210] (Infrared absorber (c))
[0211] c1: Indium Tin Oxide
[0212] c2: Cesium-containing tungsten oxide (manufactured by Sumitomo Metal Mining Co., Ltd., product name "YMF-02AS")
[0213] (Leveling agent (d))
[0214] d1: Octamethylcyclotetrasiloxane
[0215] [Adhesive layer]
[0216] ((Meth)acrylate polymer (A))
[0217] BA: n-butyl acrylate
[0218] i-BA: Isobutyl acrylate
[0219] Vac: Vinyl acetate
[0220] HEMA: 2-Hydroxyethyl Methacrylate
[0221] MAA: Methacrylic acid
[0222] (Crosslinking agent (B))
[0223] B1: Isocyanate crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "TAKENATE D-165N")
[0224] (Ultraviolet light absorber (C))
[0225] C1: Benzophenone-based ultraviolet absorber (manufactured by Solvay Japan, product name "CYASORB UV-24")
[0226] C2: Triazine-based ultraviolet absorber (manufactured by BASF, product name "Tinuvin 477")
[0227] (Crosslinking accelerator (D))
[0228] D1: Dibutyltin dilaurate
[0229] (Silane coupling agent)
[0230] E1: 3-Glycidyloxypropyltrimethoxysilane
[0231] The following evaluations were performed using the window films produced in Examples and Comparative Examples.
[0232] (Initial adhesion of adhesive layer)
[0233] The initial adhesion of the window film produced in the embodiment and the comparative example is measured as follows. The obtained window film is cut into 25 mm wide and 100 mm long. Under an environment of 23°C and a relative humidity of 50%, the peeling sheet is peeled off from the above-mentioned window film, and the exposed adhesive layer is attached to a float glass plate with a thickness of 3 mm. At this time, the window film is attached by reciprocating pressure once with a 2kg roller, and it is used as a sample for measuring the adhesion. The obtained measurement sample is placed under the conditions of 23°C and a relative humidity of 50% for 24 hours. After placement, a tensile tester (TENSILON manufactured by ORIENTEC CORPORATION) is used to measure the adhesion (N / 25mm) of the adhesive layer under the conditions of a peeling speed of 0.3m / min and a peeling angle of 180° as the initial adhesion of the adhesive layer. In addition, the conditions not described here are measured in accordance with JIS Z0237:2009. The results are shown in Table 2.
[0234] (Heat-promoted adhesion of adhesive layer)
[0235] The heat-promoted adhesion of the window film produced in the embodiments and comparative examples is measured in the following manner. A sample for measuring the adhesion is prepared in the same manner as the initial adhesion of the adhesive layer. The obtained sample for measurement is placed at 80°C for 168 hours, and then allowed to stand at 23°C and a relative humidity of 50% for 24 hours. After standing, the adhesion (N / 25mm) of the adhesive layer is measured at a peeling speed of 0.3m / min and a peeling angle of 180° using a tensile testing machine (TENSILON manufactured by ORIENTEC CORPORATION) at 23°C and a relative humidity of 50%. In addition, the conditions not described herein are measured in accordance with JIS Z0237:2009. The results are shown in Table 2.
[0236] (Moisture-heat-promoted adhesion of adhesive layer)
[0237] The heat-moisture-promoted adhesion of the window films prepared in the embodiments and comparative examples was measured in the following manner. A sample for measuring the adhesion was prepared in the same manner as the initial adhesion of the adhesive layer. The obtained sample for measurement was placed at 60°C and a relative humidity of 95% for 168 hours, and then allowed to stand at 23°C and a relative humidity of 50% for 24 hours. After standing, a tensile tester (TENSILON manufactured by ORIENTEC CORPORATION) was used to measure the adhesion (N / 25mm) of the adhesive layer at a peeling speed of 0.3m / min and a peeling angle of 180° at 23°C and a relative humidity of 50%. In addition, the conditions not described herein were measured in accordance with JIS Z0237:2009. The results are shown in Table 2.
[0238] (Storage modulus G' of adhesive)
[0239] The adhesive layer of the laminate of the release sheet and adhesive layer obtained when making the window film of the embodiment and the comparative example was laminated in multiple layers to make a laminate with a thickness of 800 μm. A cylinder with a diameter of 8 mm (height of 800 μm) was punched out from the laminate of the adhesive layer obtained and used as a sample for storage modulus measurement.
[0240] For the sample for measurement, according to JIS K7244-1, a viscoelasticity measuring device (MCR301 manufactured by Anton Paar) was used to measure the storage modulus by the torsion shear method under the conditions of a measurement temperature range of -20 to 140°C, a measurement frequency of 1 Hz, and a heating rate of 4°C / min. The storage modulus at 23°C and 80°C was calculated from the measurement results. Furthermore, the ratio of the storage modulus of the adhesive layer at 23°C to the storage modulus of the adhesive layer at 80°C (the ratio of the change in the storage modulus) was calculated from the obtained storage moduli at 23°C and 80°C. The results are shown in Table 2.
[0241] (Evaluation of Gel Fraction of Adhesive)
[0242] The laminate of the release sheet and the adhesive layer obtained when making the window film of the embodiment and the comparative example was cut into a size of 50 mm × 50 mm, and the adhesive layer was wrapped in a polyester mesh (product name: Tetoron Mesh #200), and its mass was weighed with a precision balance. The mass of the above-mentioned mesh alone was subtracted from the weighed value to calculate the mass of the adhesive itself. The mass at this time was set as M1.
[0243] Next, the adhesive wrapped in the above-mentioned polyester mesh is immersed in ethyl acetate at room temperature (23°C) for 24 hours. Then take out the mesh and air-dry it for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and further dry it in an oven at 80°C for 12 hours. After drying, weigh its mass with a precision balance. Subtract the mass of the above-mentioned mesh alone from the weighed value to calculate the mass of the adhesive itself. The mass at this time is set to M2. Using the obtained M1 and M2, the gel fraction is calculated by the following formula. The results are shown in Table 2.
[0244] Gel fraction (%) = (M2 / M1) × 100
[0245] (Optical properties of window films)
[0246] The visible light transmittance, ultraviolet transmittance and near infrared transmittance of the window film are measured as follows. The peeling sheet is peeled off from the window film obtained in the embodiment and the comparative example, and the exposed adhesive layer is attached to a float glass plate with a thickness of 3 mm. According to JIS A 5759:2016, the window film is irradiated with light in the wavelength range of 300 to 2500 nm using an ultraviolet visible near infrared spectrophotometer (UV-3600 manufactured by Shimadzu Corporation) to measure the light transmittance of the window film. The light transmittance in the wavelength range of 300 to 380 nm (ultraviolet transmittance), the light transmittance in the wavelength range of 780 to 2500 nm (near infrared transmittance) and the light transmittance in the wavelength range of 380 to 780 nm (visible light transmittance) are calculated from the measurement results. The results are shown in Table 2.
[0247] (Evaluation of removability)
[0248] The re-peelability of the window film is evaluated in the following manner. When measuring the adhesion (initial adhesion, heat-promoted adhesion and wet-heat-promoted adhesion) of the adhesive layer, the glass surface after the adhesive layer is peeled off is visually observed, and the residual adhesive is evaluated according to the benchmark shown below to evaluate the re-peelability. In addition, the adhesive layer is attached to the float glass in the same manner as the determination of the adhesion of the adhesive layer, and then the adhesive layer is peeled off by manual operation, and the residual adhesive is evaluated according to the benchmark shown below to evaluate the re-peelability. The results are shown in Table 2. The results shown in Table 2 are the results of a comprehensive evaluation of the re-peelability when the adhesion is measured and the re-peelability when peeled off based on manual operation.
[0249] ◎: No residual glue
[0250] ○: Although there is slight blur or adhesive residue, it can be easily wiped off
[0251] △: Glue residue is generated in some parts
[0252] ×: Glue residue is left on the entire surface of the attachment
[0253] [Table 2]
[0254]
[0255] According to Table 2, it was confirmed that the initial adhesion and heat-accelerated adhesion of the window films of Examples 1 to 6 were within the prescribed ranges, and the initial adhesion and re-peelability were excellent.
[0256] Industrial Applicability
[0257] The window film of the present invention can be used by being attached to windows of mobile bodies such as automobiles, windows of buildings, etc. In addition, the window film of the present invention can be applied by being attached to glass other than window glass or glass substitute materials (for example, plastics, etc.).
[0258] Description of Reference Numerals
[0259] 1: window film; 10: substrate; 11: adhesive layer; 12: hard coating layer.
Claims
1. A window film comprising a substrate and an adhesive layer disposed on one main surface of the substrate, wherein: After being placed at 23°C and 50% relative humidity for 24 hours, the adhesive layer has an adhesion to the float glass of 1N / 25mm or more. The adhesive strength of the adhesive layer to the float glass after being left to stand at 80° C. for 168 hours was 18 N / 25 mm or less.
2. The window film according to claim 1, wherein: The ratio of the storage elastic modulus of the adhesive layer at 23° C. to the storage elastic modulus of the adhesive layer at 80° C. is 3.5 or less.
3. The window film according to claim 1 or 2, wherein: The adhesive strength of the adhesive layer to the float glass after being left to stand at 60° C. and a relative humidity of 95% for 168 hours was 22 N / 25 mm or less. 4 . The window film according to claim 1 , further comprising a hard coating layer disposed on the other main surface of the substrate.
5. The window film according to claim 1 or 2, wherein: The window film has ultraviolet light absorption property.
6. The window film according to claim 1 or 2, wherein: The window film has infrared absorption property.